Analisis Dampak Tukang Sayur Keliling Terhadap Pendapatan Pedagang di Pasar Sebaung Kecamatan Gending - Faiqotul Karimah; Nadila Syalsadila; Alviana Novita Sari (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2024)
This research aims to analyze the impact of vegetable vendors on the income of market traders who have experienced a decline in income in markets in the Gending sub-district, Probolinggo district. This research was conducted from October to November 2023. The research location was determined proportionally (intentionally). This research used descriptive research with a qualitative approach. This descriptive research takes an analytical study of the impact of mobile vegetable sellers on the income of traders in markets in Gending sub-district. Data collection was carried out through interviews, observation and documentation. As mobile greengrocers, they select and obtain vegetables to be sold based on freshness quality, and local customer references include working with local farmers to ensure quality supplies or direct supplies to the Probolinggo market center. To determine the price of vegetables, greengrocers consider supply costs, operations and reasonable profits. Mobile vegetable sellers also pay attention to local market prices to remain competitive. Mobile vegetable vendors use appropriate storage and packaging methods and ensure that the vehicles used are equipped with safe facilities to maintain the freshness of vegetables during the journey.